ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE FULMER SCORE DAN ZMIJEWSKI SCORE PADA PT GOZCO PLANTATIONS, TBK - Putri, Debi Eka; Ervina, Nelly; Silaen, Musa Fernando; Syahputri, Anggraini; Kesuma, Indrawati Mara (Universitas Mahendradatta Denpasar, 2025)
Abstract - This study aims to analyze the financial distress condition of PT. Gozco Plantations, Tbk using the Fulmer Score and Zmijewski Score methods and determine the more accurate method. The research data are secondary data obtained from the Indonesia Stock Exchange website (www.idx.co.id). The data analysis techniques used are descriptive qualitative and comparative analyses. The results show that: First, the Fulmer Score method indicates that the company was at risk of bankruptcy during the 2014-2023 period due to declining profits, negative operating cash flows and working capital, as well as decreased assets and equity. Second, the Zmijewski Score method indicates that the company was not at risk of bankruptcy due to reduced debts and its ability to generate profits. Third, the Fulmer Score method is more accurate in measuring bankruptcy risk, with 80% of results in the danger zone compared to 20% for the Zmijewski Score.